Sentiment analysis on mobile operators’ customer review - Hossain, Mohammed Mohibul; Rahman, Md. Mostafizur; Seaum, Samin Yeasar; Ahmed, Akil (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.